Developmental and phylogenetic characteristics of stellantchasmus falcatus (Trematoda: Heterophyidae) from Thailand - Sripalwit,P. (Korean Journal of Parasitology, 2015)
© 2015, Korean Society for Parasitology and Tropical Medicine This study aimed to investigate the infection status, worm development, and phylogenetic characteristics of the intestinal trematode, Stellantchasmus falcatus. The metacercariae of S. falcatus were detected only in the half-beak (Dermogenus pusillus) out of the 4 fish species examined. Their prevalence was 90.0%, and the intensity of infection was 919 metacercariae on average. Worms were recovered from 33 (97.1%) of 34 chicks that were experimentally infected with 200 S. falcatus metacercariae each, and the average recovery rate was 43.0%. The body size and inner organs of S. falcatus quickly increased in the experimental chicks over days 1-2 post-infection (PI). In addition, ITS2 sequence data of this parasite were analyzed to examine the phylogenetic relationships with other trematodes using the UPGMA method. The results indicated that the ITS2 sequence data recorded from trematodes in the family Heterophyidae appeared to be monophyletic. This study concluded that D. pusillus serves as a compatible second intermediate host of S. falcatus in Thailand and that S. falcatus can develop rapidly in the experimental chicks. Data collected from this study can help to close the gap in knowledge regarding the epidemiology, biology, and phylogenetic characteristics of S. falcatus in Thailand.